John Heavyside’s Manual of Psalmody for Public Worship of 1839 : South Africa’s first Anglican collection of metrical psalms and hymns - Bethke, Andrew-John (Muziki : Journal of Music Research in Africa, 2019)
This article examines and contextualises John Heavyside’s Manual of Psalmody for Public Worship (hereafter simply referred to as the Manual). It was published in 1839 in Grahamstown which, at the time, was in the Cape Colony. The Manual is the earliest South African Anglican collection of metrical psalms and hymns from the era. The article seeks to demonstrate that the Manual’s editor clearly understood and appreciated the gradual popularisation of hymnody after the monopoly of metrical psalmody had been broken in 1820. It shows, too, that he was keen to introduce his own congregation to the newest international trends, not only from Anglican circles, but also Methodist and Congregational hymnody. It continues by concentrating on Heavyside’s compilation, examining its contents and attempting to deduce which sources were consulted for the choice of hymns. An examination of Heavyside’s editorial techniques is included to determine his contextual positioning of certain hymns. The analysis includes a commentary on the four locally composed hymns which form part of the Manual, along with an introduction to their possible author. The article concludes with a brief examination of how the hymnbook was received by the local community.
paid